Determination of antioxidant and immune responses with bile acids supplementation in geese - Jianwen CAO; Lei YANG; Guangpei XU (Kafkas Universitesi Veteriner Fakültesi Dergisi)
This study investigated the impact of varying levels of bile acids (BAs) on the immune and antioxidant functions in the geese. A total of 168 male Hortobágyi geese, aged 28 days, were randomly assigned to four groups: the control group received a basic diet, while the other groups received diets supplemented with 75 mg/kg, 150 mg/kg, and 300 mg/ kg of BAs. The trial lasted for 35 days, after which samples were collected for the analysis of antioxidant and immune indicators. Results showed that, compared to the control group, the supplementation of BAs in the feed did not significantly affect the indices of immune organs or serum immune levels (P>0.05). However, a supplementation with 300 mg/kg BAs significantly increased the expression of IL-10 mRNA in the geese"s spleens. Regarding antioxidant indicators, the addition of 150 mg/kg and 300 mg/kg BAs significantly enhanced the serum levels of Superoxide Dismutase (SOD), Glutathione Peroxidase (GSH-Px), and Total Antioxidant Capacity (T-AOC) (P<0.05), as well as upregulated the expression of liver Nrf2, GPX-1 and SOD1 mRNA. In conclusion, within the range of BAs supplementation used in this experiment, the improvement in geese"s immune status was limited. Although higher levels of BAs might influence the immune status, the supplementation significantly enhanced the antioxidant capacity in serum and liver, with an optimal addition level of 150 mg/kg.